2018
DOI: 10.1590/1983-21252018v31n204rc
|View full text |Cite
|
Sign up to set email alerts
|

Post-Harvest Storage of Papaya Fruits Coated With Extracts of Leaves and Fruits of Neem

Abstract: The objective of the present work was to evaluate the use of extracts of leaves and fruits of neem (Azadirachta indica Juss) as coating for papaya Formosa fruits aiming to maintain their quality during post-harvest storage. A completely randomized experimental design in a 5x5 factorial arrangement was used, with 3 replications of 2 papaya fruits per plot. The treatments consisted of five coatings with extracts of neem leaves and fruits (leaf extracts at 5 and 10%, fruit extracts at 5 and 10% and a control trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
2
1
0
2
Order By: Relevance
“…Results above that observed by Silva (2016), which found an average of approximately 0.1% in fruits of papaya "Tainung 1". Souza et al (2014a) obtained an average of 0.09% of citric acid for papayas of the same variety, as well as found by Freitas et al (2018). Silva (2019) obtained mean values equal to 82 mg/100 g of vitamin C for fruits at the beginning of storage time, being found in this study an average of 38.01 mg/100 g. Nunes et al (2017) found mean values above 60 mg/100 g of vitamin C in Formosa papayas coated with cassava starch.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Results above that observed by Silva (2016), which found an average of approximately 0.1% in fruits of papaya "Tainung 1". Souza et al (2014a) obtained an average of 0.09% of citric acid for papayas of the same variety, as well as found by Freitas et al (2018). Silva (2019) obtained mean values equal to 82 mg/100 g of vitamin C for fruits at the beginning of storage time, being found in this study an average of 38.01 mg/100 g. Nunes et al (2017) found mean values above 60 mg/100 g of vitamin C in Formosa papayas coated with cassava starch.…”
Section: Resultssupporting
confidence: 87%
“…The treatments that provided greater firmness in the pulp was T6, and T5 (covering more concentrated in agar and pomegranate seed oil) was the treatment that provided less firmness. Souza et al (2014a) found a mean of approximately 5.0 N at 7 days postharvest, which can also be observed by Freitas et al (2018) when working with the covering of papayas Figure 2. VOT C = Vitamin C analyzes (in mg/100 g -A); pH (B); FPP = Pulp Firmness (in N -C); FFT = fruit firmness (in N -D) of 'Tainung 01 Formosa' papaya coated with agar solution and pomegranate seed oil after 10 days of storage (17.…”
Section: Resultssupporting
confidence: 63%
“…Although a previous study did not report significant differences between the total soluble solid content of ozone-treated and untreated papayas (Bataller et al., 2012), the soluble sugars ratio between sucrose and glucose/fructose in ripe fruits could be altered. Recently, the treatment of unripe papaya with plant extracts, such as Neem ( Azadirachta indica Juss), has been proposed as an alternative for maintaining food quality for a longer postharvest period (Freitas et al., 2018). However, as with ozone treatment, the observation of fruit quality maintenance for a longer period was not accompanied by an evaluation of soluble sugar metabolism.…”
Section: Pulp Sweetness As a Results Of Papaya Primary Metabolismmentioning
confidence: 99%
“…Perdas pós-colheita desses frutos ocorrem principalmente pela frequência respiratória elevada, produção de etileno que estimula o amadurecimento e deterioração fúngica. Os danos ocorrem por fatores fisiológicos, patológicos e a transpiração ocasiona o murchamento do fruto, acelerando o processo de degradação (Andrade & Vieira, 2016;Martins & Siqueira, 2017) Outro fator que aumenta a incidência de perdas consiste nas doenças pós-colheita, ou seja, além da degradação decorrente do metabolismo interno, os frutos também passam por deterioração microbiana (Dantas et al, 2018;Freitas et al, 2018).…”
Section: Introductionunclassified